PENERAPAN SISTEM INFORMASI AKUNTANSI SEBAGAI UPAYA MENINGKATKAN KUALITAS LAPORAN KEUANGAN PADA PERUMDA AIR MINUM WAIR PU’AN KABUPATEN SIKKA - Fransiska Amelya Agata; Maria Nona Dince; Yoseph Darius Purnama Rangga (Jurnal Projemen UNIPA, 2025)
This research aimed to know and analyze the implementation of financial accounting information systems in improving the quality of financial statements at the Wair Pu'an Regional Drinking Water Public Company, Sikka Regency. Data were collected using observation, interview and documentation methods. This research used a qualitative descriptive method in which the researcher described and analyzed the implementation of financial accounting information systems. The results showed that the implementation of financial accounting information systems had already used SISKA Application but it had a lack of relevant time in presenting and inputting the financial statement.